Pemanfaatan Tumbuhan Sebagai Pewarna Alami Oleh Suku Dayak Randu Di Desa Suka Damai Kabupaten Melawi - Riza Linda,, Dwi Rahmawati Rusja, Elvi Rusmiyanto Pancaning Wardoyo, (Universitas Tanjungpura, 2018)
West Kalimantan is one of regions of Indonesia which has a plentiful biodiversity. One of the utilization of its biodiversity is natural dyes. Natural dyes are obtained by exctracting the pigment of plant organs such as fruits, flowers, leaves, skins, tubers, and rhizomens. The Dayaks utilize the natural dye plants to dye yarns and fabrics. This research aims to find out the types of plants, citation frequency and the informant agreement ration of the natural dyes used by the Dayak Randu people. This research used purposive samplimg by involving 23 responders of Dayak Randu people in Suka Damai village, Pinoh Utara District Melawi Regency. This results show that there are the types of natural dyes utilized for coloring yarns, nails and food. Curcuma domestica and Pandanus amaryllifolius have 100% cition frequency, while the informant agreement ration of yarn dye is 0.66%, nail dye is 0,75% and food dye is 0,80%.